1
$\begingroup$

If $a \neq 0$ and if one root of the equation $ax^2+bx+c=0$ is the square of the other, prove that: $$b^3+a^2c+ac^2=3abc.$$

My Attempt: Given: $$ax^2 + bx + c=0$$ Let $\alpha $ and $\beta $ be the roots of the equation. $$\alpha + \beta = \dfrac {-b}{a}$$ $$\alpha . \beta = \dfrac {c}{a}$$ According to the question: $$\alpha = \beta^2 $$

$\endgroup$
  • $\begingroup$ What if $a=0\,$? If your question relies on additional assumptions, please spell them out. $\endgroup$ – dxiv Aug 19 '17 at 5:46
  • $\begingroup$ @dxiv, There are no more assumptions. The question is exactly the same what I have typed. $\endgroup$ – pi-π Aug 19 '17 at 6:02
  • $\begingroup$ If $a=0, b=1, c=-1$ then the only root is $x=1$ which is obviously its own square. However $b^2+a^2c+ac^2 = 1 \ne 0 = 3abc\,$, so the conclusion you propose doesn't follow. $\endgroup$ – dxiv Aug 19 '17 at 6:05
  • $\begingroup$ @dxiv, What is the meaning of quadratic equation if $a=0$? $\endgroup$ – pi-π Aug 19 '17 at 6:07
  • $\begingroup$ Where was quadratic mentioned before this last comment? All I am getting at is that's important that you make sure to give the full context to a question in order to elicit unambiguous answers (same as here). $\endgroup$ – dxiv Aug 19 '17 at 6:08
1
$\begingroup$

So, we have $$\dfrac ca=\alpha\beta=\beta^3$$

$$-\dfrac ba=\alpha+\beta=\beta^2+\beta$$

Cube both sides using $$(p+q)^3=p^3+q^3+3pq(p+q)$$

Replace the values of $\beta^3,\beta^2+\beta$

$\endgroup$
  • $\begingroup$ Cubing both sides of which equation? $\endgroup$ – pi-π Aug 19 '17 at 6:03
  • $\begingroup$ @blue_eyed_..., Not equation, but the relation : $$-\dfrac ba=\beta^2+\beta$$ $\endgroup$ – lab bhattacharjee Aug 19 '17 at 6:04
1
$\begingroup$

$$\alpha + \beta = \dfrac {-b}{a}$$ $$\alpha . \beta = \dfrac {c}{a}$$ Substitute $$\alpha = \beta^2$$ into previous equations,

$$a(\beta^2+\beta) = a\beta(\beta+1) = - b\tag{1}$$

$$a\beta^3 = c\tag{2}$$

Cube equation $(1)$,

$$a^3 \beta^3 (\beta^3 + 3 \beta^2 + 3 \beta + 1) = -b^3$$ Using equation $(2)$, $$a^2 c (\beta^3 + 3 \beta^2 + 3 \beta + 1) = -b^3$$

$$a c (a\beta^3 + 3a\beta( \beta + 1) + a) = -b^3$$

Using equation $(1)$ and $(2)$,

$$a c (c - 3b + a) = -b^3$$

$$ac^2-3abc+a^2c=-b^3$$

$$b^3+ac^2+a^2c = 3abc$$

$\endgroup$
0
$\begingroup$

Alternatively: $$\left(\frac{-b-\sqrt{b^2-4ac}}{2a}\right)^2=\frac{-b+\sqrt{b^2-4ac}}{2a} \Rightarrow$$ $$b^2-2ac+ab=(a-b)\sqrt{b^2-4ac} \Rightarrow$$ Squaring and then dividing both sides by $4a$ will prove the claim.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.